Adherence to Hepatitis B Antiviral Therapy: A Qualitative Study. (May 2017) - Polis, Suzanne; Zablotska-Manos, Iryna; Zekry, Amany; Maher, Lisa
Abstract : Hepatitis B virus (HBV) antiviral therapies potentially suppress HBV viral load to an undetectable level reducing the risk of progressive liver disease and the development of HBV-related hepatocellular carcinoma. Adherence to antiviral therapies is imperative to achieve and maintain viral suppression. To date, there has been limited research on adherence to HBV therapies. Our study aimed to explore factors influencing adherence to antiviral therapy. A total of 29 participants consented to in-depth qualitative interviews at three outpatient clinics in Sydney, New South Wales, Australia. Interviews were digitally recorded and transcribed. Transcripts were initially classified as adherent or nonadherent and thematic analysis was used to identify dominant themes. Adherent behavior was reported by 59% ( n = 17) of participants. Several themes influenced adherence including routine, fear of HBV-related disease progression, clinician–patient communication, treatment knowledge, and forgetfulness. To our knowledge, this is the first qualitative study to explore adherence to HBV antiviral therapy. An interplay of several dominant themes emerged from our data including fear of chronic HBV disease progression, clinician–patient communication, treatment knowledge, routine, and forgetfulness. Study findings have the potential to change nursing clinical practice, especially the way nurses and other clinicians target key HBV treatment messages and education, while monitoring adherence.